A dimer of the negatively charged carbonyl cluster {Ir4(CO)11−}2 bonded by a single Ir−Ir bond, and comparison with the singly bonded (C60−)2 dimer. Issue 6 (6th February 2023) - Sobov, Pavel A.; Shestakov, Alexander F.; Kuzmin, Alexey V.; Khasanov, Salavat S.; Otsuka, Akihiro; Yamochi, Hideki; Kitagawa, Hiroshi; Konarev, Dmitri V.
Abstract: Reduction of the Ir4 (CO)12 cluster by two equivalents of Cp*2 Cr (Cp* is η 5 ‐Me5 C5 ) produces the (Cp*2 Cr + )2 {Ir4 (CO)11 − }2  ⋅ 4 C6 H4 Cl2 complex. Two Ir4 (CO)11 − anions are bonded by a single Ir−Ir bond in the anionic {Ir4 (CO)11 − }2 dimer. The bond length is 2.8339(5) Å at 100 K. Therefore, clusters can form metal‐metal bonded dimers under reduction. The {Ir4 (CO)11 − }2 dimers do not dissociate to paramagnetic species up to 340 K and even higher temperatures that indicates their high stability. DFT calculations show that dimerization of clusters can occur due to the loss of one CO group in neutral or anionic clusters. Dimerization of anionic transition metal cluster is to a certain extend similar to dimerization of negatively charged carbon cluster – fullerene C60 ⋅ − and here we compare both types of dimers. Abstract :